THE DYNAMICS OF CHANGES OF CLINICAL INDICATORS IN DOGS FOR TREATMENT PURULENT WOUNDS BY DIFFERENT SCHEMES - Talgatova, A. T.; Dnekeshev, A. K. (Science and education №1, 2019)
The article presents the dynamics of changes in some common clinical indicators in dogs with the application of local infiltration of the hemo - novocaine blockade in combination with the homeopathic complex drug Trauma-gel in a comparative aspect of treatment of complicated superficial skin damage in the form of purulent wounds. Measuring temperature, pulse rate and respiration are mandatory methods of clinical research, which allow to assess the condition of the animal, monitor the course and predict the development of the disease, judge the effectiveness of treatment, identify complications. Novocaine blockade in the damaged area (wound) removes severe irritation of the nervous system and replaces it with a weak, qualitatively new irritation, weakening the flow of pain impulses into the cerebral cortex, thereby protecting it from functional exhaustion. In the blocked focus, novocaine, has antiacetylcholine and antitoxic effects, increases redox processes, regulates carbohydrate, nitrogenous and phosphoric exchanges, thereby maintaining the body at the level of a favorable course of physiological processes. The results of our own research are recommended for use in the treatment of complex inflamed purulent wounds in dogs, as one of the methods of pathogenetic therapy.В статье даны динамика изменения некоторых общих клинических показателей у собак при применении местно-инфильтрационно гемо-новокаиновую блокаду в сочетании с гомеопатическим комплексным препаратом Травма-гель в сравнительном аспекте лечения осложненных поверхностных повреждении кожи в виде гнойных ран. Измерение температуры, частоты пульса и дыхания являются обязательными способами клинического исследования, которые позволяют оценить состояние животного, контролировать течение и прогнозировать развитие болезни, судить об эффективности лечения, выявить осложнения. Новокаиновая блокада в поврежденной области (ране), снимает сильное раздражение нервной системы и заменяет его слабым, качественно новым раздражением, ослабляя при этом поступление болевых импульсов в кору головного мозга, охраняя тем самым ее от функционального истощения.
Keywords: научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel; научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- ветеринария -- гнойные раны -- болезни собак -- treatment of purulent wounds in dogs -- changes in general clinical indicators for purulent wounds -- hemo-novocaine blockade -- homeopathic complex drug trauma-gel